Nutritional recommendation in adolescent - Giannini, Denise Tavares (Adolescência e Saúde, 2007)
Background: Adolescence constitutes the last phase of growth and development period of the vital cycle. It is characterized by intense anatomical, physiological, and psychological changes. To promote a proper growth, the adolescents nutrition, must be appropriate: with healthy, balanced in quantity and quality nutrients. Objective: Review of the literature about new nutritional needs in adolescence. Methods: National and international literature review in this life period in Medline database, comprising the period of 2000-2006. Conclusion: Adolescence is a peculiar stage of human growth and development, therefore the health professional is responsible to have a concern with the adequate food intake, in this life phase they need greater amounts of nutrients to guarantee the bodily changes. Due to is necessary attention over some nutrients that are involved in the growth with adequate energy, protein, vitamins mainly A, C and D and minerals as iron, calcium and zinc.